2004
DOI: 10.1126/science.1102443
|View full text |Cite
|
Sign up to set email alerts
|

Hematotoxicity in Workers Exposed to Low Levels of Benzene

Abstract: Benzene is known to have toxic effects on the blood and bone marrow, but its impact at levels below the U.S. occupational standard of 1 part per million (ppm) remains uncertain. In a study of 250 workers exposed to benzene, white blood cell and platelet counts were significantly lower than in 140 controls, even for exposure below 1 ppm in air. Progenitor cell colony formation significantly declined with increasing benzene exposure and was more sensitive to the effects of benzene than was the number of mature b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
412
5
17

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 553 publications
(452 citation statements)
references
References 18 publications
18
412
5
17
Order By: Relevance
“…24 This study found evidence of low-level benzene concentrations having an effect on peripheral blood WBCs. This finding is consistent with other studies conducted in China among shoemakers, [25][26][27] but contrary to a study in the Netherlands. 28 It is possible that the doserelationship between low benzene exposure in exposed workers and the life exposure in internal controls was modified by other factors in the Netherlands study, such as small numbers, worker protection, and life factors (e.g.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…24 This study found evidence of low-level benzene concentrations having an effect on peripheral blood WBCs. This finding is consistent with other studies conducted in China among shoemakers, [25][26][27] but contrary to a study in the Netherlands. 28 It is possible that the doserelationship between low benzene exposure in exposed workers and the life exposure in internal controls was modified by other factors in the Netherlands study, such as small numbers, worker protection, and life factors (e.g.…”
Section: Discussioncontrasting
confidence: 54%
“…Lan et al 25 reported that the decreases in white blood, red blood, and platelet counts were observed in workers exposed to relatively low levels of benzene (1 ppm). The findings were particularly robust because of the extensive exposure assessment over a 16-month period.…”
Section: Discussionmentioning
confidence: 99%
“…Although they are also secreted by other cells, platelets remain the most abundant and the most rapidly available source for these CXC-chemokines (17,18). It is well established that benzene lowers peripheral platelet counts (7)(8)(9), raising the possibility that our finding could be explained entirely or in part by a decrease in platelet counts among the exposed subjects. However, we determined that the absolute platelet count did not significantly impact on the difference in expression of PF4 and CTAP-III between benzene exposed and unexposed subjects by using linear regression on the natural logarithm of each protein adjusted and unadjusted for platelet count (Table 3).…”
Section: Confirmation Of Protein Biomarkersmentioning
confidence: 46%
“…Benzene is an established cause of acute myeloid leukemia and myelodysplastic syndromes and may play a role in lymphocytic leukemias and non-Hodgkin lymphoma in humans (1)(2)(3)(4)(5)(6). Additionally, changes in blood and bone marrow consistent with hematotoxicity are recognized in humans and experimental animals (7)(8)(9). Benzene also produces immunosuppressive effects in exposed animals and humans and has been shown to increase susceptibility to tuberculosis and other infectious agents (10,11).…”
mentioning
confidence: 99%
“…Além da utilização industrial, a presença de benzeno na fumaça de veículos automotivos e do cigarro contribui para contaminação ambiental Qu et al, 2000;Turteltaub, Mani, 2003;Fustioni et al, 2005). O controle da exposição em países em desenvolvimento nem sempre é satisfatório e, assim, relatos clínicos de intoxicação ocupacional e ambiental pelo benzeno ainda são encontrados na literatura (Waidyanatha et al, 2001;Lan et al, 2004;Stokstad, 2004;Qu et al, 2005;Kim et al, 2006).…”
Section: Introductionunclassified